2021
DOI: 10.31004/jptam.v5i2.1384
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Hasil Belajar Siswa dalam Pembelajaran Tematik Terpadu Menggunakan Model Pembelajaran Kooperatif Tipe Make A Match Kelas IV SD Negeri 20 Indarung

Abstract: Penelitian ini bertujuan untuk mendeskripsikan penggunaan model pembelajaran Kooperatif Tipe Make A Match untuk meningkatkan hasil belajar siswa dalam pembelajaran tematik terpadu di kelas IV SD Negeri 20 Indarung. Penelitian ini merupakan penelitian tindakan kelas(Classroom Action Research), yang menggunakan pendekatan kualitatif dan kuantitatif. Penelitian ini dilaksanakan dua siklus dengan tiga kali pertemuan yang meliputi empat tahapan yaitu perencanaan, pelaksanaan, pengamatan, dan kemudian refleksi. Subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…Apart from that, research conducted by Pratama, Sopandi, and Hidayah [23] can be concluded that the RADEC learning model can improve students' high-level thinking abilities in elementary schools as seen based on the average post-test score for the RADEC class of 70.08 compared to The average pretest score was 40.44, which means there was an increase of 29.54. This is also supported by research by Fuziani et al [24] based on research entitled "The influence of the RADEC learning model on elementary school students' higher order thinking skills". The results obtained were that during the implementation of the research there were significant changes in the test results carried out before and after implementing the RADEC learning model, so that this RADEC learning model was considered capable of being another solution for improving HOTS.…”
Section: Implementation Stagesupporting
confidence: 53%
“…Apart from that, research conducted by Pratama, Sopandi, and Hidayah [23] can be concluded that the RADEC learning model can improve students' high-level thinking abilities in elementary schools as seen based on the average post-test score for the RADEC class of 70.08 compared to The average pretest score was 40.44, which means there was an increase of 29.54. This is also supported by research by Fuziani et al [24] based on research entitled "The influence of the RADEC learning model on elementary school students' higher order thinking skills". The results obtained were that during the implementation of the research there were significant changes in the test results carried out before and after implementing the RADEC learning model, so that this RADEC learning model was considered capable of being another solution for improving HOTS.…”
Section: Implementation Stagesupporting
confidence: 53%
“…Then about 38 articles were reviewed and analyzed, consisting of national and international journals. The references that the researchers got are listed in the following table: Talking Stick Learning Model (Sultan & Kadir, 2022), (Ramadhani, 2021), (Azizah & Nugraha, 2018), (Afifah et al, 2020), (Vidayanti et al, 2017), (Alfiani, 2021), (Faradita, 2018), (Atma et al, 2022), (Hasrudin & Asrul, 2020), (Setiawan et al, 2019), (Nelpi & Farida, 2020), (Salwa et al, 2018), (Rahmi et al, 2018), (Purnamayanti & Tegeh, 2020), (Kamarudin et al, 2021), (Saihu, 2020), (Gunardi & Ramadewi, 2022), (Utami et al, 2020), (Aslami et al, 2019), (Ayuni et al, 2017), (Fajrin, 2018), (Lestari et al, 2017), (Huda, 2017) Learning Outcomes Elementary Students with Talking Stick (Noviyanti, 2020), (Suwarni, 2020), (Sihotang, 2017), (Partami & Rendra, 2019), (Adiko & Djafar, 2022b), (Ritonga et al, 2021), (Pantas & Surbakti, 2020), (Ratmawati & Ihtiari, 2021), (Suhartin, 2017), (Hayun & Ataphary, 2019), (Wulandari, 2021), (Noviana & Triwulan Desta, 2018), (Yopo et al, 2021), (Septianingrum & Hamimah, 2021),…”
Section: Methodsmentioning
confidence: 99%
“…Dari penjelasan di atas terdapat beberapa penelitian yang sejenis dengan judul peneliti di antaranya adalah penelitian dari (Hasibuan & Sukma, 2021) berpendapat bahwa Model Kooperatif Tipe (Numbered Head Together) NHT di kelas IV SD dapat meningkatkan hasil belajar peserta didik pada pembelajaran tematik terpadu. Begitu juga dengan penelitian dari (Astrawan, 2013).…”
Section: Pendahuluanunclassified